2020
DOI: 10.1111/jce.14452
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral anticoagulation therapy in the first 3 months after the diagnosis of atrial fibrillation in Israel: A population‐based study

Abstract: Introduction: Oral anticoagulation (OAC) therapy reduces the risk of ischemic stroke in patients with atrial fibrillation (AF) while increasing the risk of bleeding.Recently, non-vitamin K antagonist oral anticoagulants (NOACs) have become available with lower rates of intracranial bleeding, and some of them have presented a reduced risk of major bleeding. The purpose of this study is to evaluate the change in purchasing patterns of OACs (both warfarin and NOACs) over time in patients with AF according to stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…[40] When it comes to overtreatment, between 0.6% and 79.8% of patients at low risk of stroke who did not need any antithrombotic medication received treatment, which would be considered to be overtreatment. [18,22,26,31,33,35,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Recent studies that investigated trends in guideline adherence have shown substantial improvements in guideline adherence over time. Cowan et al [63] reported an increase in the prescription of OACs (by 30.6%) and a decline in the prescription of antiplatelet agents (by 26.8%) over a 10-year period in AF patients at high risk of stroke.…”
Section: Non-adherence To Guidelinesmentioning
confidence: 99%
“…[40] When it comes to overtreatment, between 0.6% and 79.8% of patients at low risk of stroke who did not need any antithrombotic medication received treatment, which would be considered to be overtreatment. [18,22,26,31,33,35,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Recent studies that investigated trends in guideline adherence have shown substantial improvements in guideline adherence over time. Cowan et al [63] reported an increase in the prescription of OACs (by 30.6%) and a decline in the prescription of antiplatelet agents (by 26.8%) over a 10-year period in AF patients at high risk of stroke.…”
Section: Non-adherence To Guidelinesmentioning
confidence: 99%
“…However, the rates found in literature vary. Few studies showed lower OAC treatment rates of 50% or less.Those results were demonstrated in early European registry conducted during[2003][2004]6 in the preliminary results from the NCDR PINNACLE registry conducted in the USA during 2008-2012,8 in the part conducted in Asia of RE-LY and GLORIA-AF registries during 2008-2011 and 2011-2014, respectively,7,11 and in a single study from Israel conducted during 2008-2015 10. Lower OAC treatment rates in these studies can be explained by temporal and geographic factors, meaning less treatment during early years after guidelines introduction and less treatment in Asia.…”
mentioning
confidence: 82%
“…5 Despite guidelines, OAC treatment was found to be suboptimal among patients with AF. That means there is underuse of OACs among high-risk patients [6][7][8][9][10][11][12][13] while overuse among low-risk patients. [10][11][12][13][14] Contrary to expectations, the contribution of the DOACs introduction has been only modest at first.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations